Systematic identification of immunodominant CD4(+) T cell responses to HpaA in Helicobacter pylori infected individuals - Hu, Jian (Oncotarget, 2016)
In mice, antigen-specific CD4(+) T cell response is indispensible for the protective immunity against Helicobacter pylori (H. pylori). It has been demonstrated that neuraminyllactose-binding hemagglutinin (HpaA) immunization protected mice from H. pylori infection in a CD4(+) T cell dependent manner. However, much remains unclear concerning the human CD4(+) T cell responses to HpaA. We conducted a systematic study here to explore the immunodominant, HpaA-specific CD4(+) T cell responses in H. pylori infected individuals. We found that HpaA-specific CD4(+) T cell responses varied remarkably in their magnitude and had broad epitope-specificity. Importantly, the main responses focused on two regions: HpaA76-105 and HpaA130-159. The HLA-DRB1*0901 restricted HpaA142-159 specific CD4(+) T cell response was the most immunodominant response at a population level. The immunodominant epitope HpaA142-159 was naturally presented and highly conserved. We also demonstrated that it was not the broad peptide specificity, but the strength of HpaA specific CD4(+) T cell responses associated with gastric diseases potentially caused by H. pylori infection. Such investigation will aid development of novel vaccines against H. pylori infection.